Air Pollution in Karnataka: A Causal Analysis - Subramanyam, Chandrasekhar; Khatua, Sidharth; Enna; Misra, Siddharth (International Journal of Psychosocial Rehabilitation, 2019)
Purpose: This research aims to highlight Major contributing factors towards air pollution in Karnataka and provide necessary recommendation to government and other stakeholders. Design/Methodology/ Approach: The data was collected from data.gov.in of sample size 2400 observation and 12 variables. The framework that was used to do the analysis were problem identification, Data exploration, Model building, Solution implementation and monitoring. Training the sample data and validating the results on the test data were the approach taken furthermore programming tool R, Excel and SPSS was used to explore, recode data and build model. Findings:From the analysis,it is observed that chemical components likeNO2and So2, cities like Devengree, Bangalore,Tumkur winter months like from October to February were the top contributors to air pollution in Karnataka. Practical Implications:Using the analysis derived, Government stakeholders can identify the cities that are impacting air pollution, understand the reason for the cause and apply stringent norms to reduce the pollutants in the air. Also educating the younger generation by providing awareness regarding the ill effects of air pollutants on heath was also recommended. Originality/ Values:Stepwise linear regression was used to estimate causal effect between PM10 and other variables, Decision Tree (CHAID) regressionused for machine learning to reduce the overall MAPE furthermore random forest regression tree was used to identify the top 10 contributing factors cause air pollution in Karnataka adding worthiness and novelty to this study.